Ecología de Vibrio cholerae en relación al fitoplancton y variables fisicoquímicas en ríos de Tucumán (Argentina) - Gaudioso de Allori, María Cristina (2007)
Ecology of Vibrio cholerae in relation to phytoplankton and physico-chemical variables in rivers of Tucumán (Argentina). Vibrio cholerae shows a great serologic diversity in relation to his O somatic antigen and we know at least 200 serogroups. About these, only O1 and O139 are responsible of epidemics and pandemics. The serogroup O1 reemerged in Latin America in 1991 after being absent from the continent for nearly a century. This bacterium survives and grows up associated to plankton, independently of appearance of human infections. From 90 th decade, there were sporadic cases of diarrhea because of Vibrio cholerae O1 in Tucumán. The aims of this paper were to study the possible relation between phytoplankton species, physico-chemical variables and V. cholerae isolations in rivers of Tucumán. There were 18 sampling in the rivers Salí and Lules from 2003 to 2005. Physico- chemical variables of water (pH, temperature, conductivity and dissolved oxygen), phytoplankton (richness and relative frequency) and V. cholerae isolations were studied in this paper. Results showed differences in water quality, with anoxic periods in the River Salí. Diatoms were conspicuous in almost all months and generally there were in percentages upper 85 %. Just Vibrio cholerae non- O1, non-O139 was isolated, specially in months warmer with alkaline pH and also with dissolved oxygen low concentration.